A Visitor to the Sami Museum - Burceva, Rita (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of the article is to study and analyse the peculiarities of one particular museum (The Sami Museum in Norway) and the conditions that form the subjective attitude of the visitor experience gained there and that strengthen the attitude towards the museum as an opportunity of spending leisure time. Case analysis is the research method used. An important feature that allows the Sami Museum to stand out among other European museums of similar purpose and functionality, it is its ability to create an offer for various target groups of visitors in a relatively small territory, making use of diverse resources: authentic objects and their copies the visitors are allowed to touch and take in their hands, the wildlife (reindeers on the grassland) and the traditional buildings of the Sami people that can be entered to see their interior, the modern technologies and the tools of public relations used purposefully, traditional cuisine, and the small shops of some products and souvenirs made by local craftsmen, convenient parking places and loyal pricing policy for families, the symbols and visitor-oriented, thought-out communication used in the museum. Based on the theoretical literature (tourism management, communication, pedagogy, psychology, social anthropology, etc.) analysis and the quality data collected during the empirical research, a model that demonstrates the impact of various conditions on the formation of the personal experience, opinion and subjective attitudes of a visitor during the visit to a museum was developed and offered for discussion.